Acute physical activity and delayed attention in primary school students. Issue 3 (18th August 2014) - Gallotta, M. C.; Emerenziani, G. P.; Franciosi, E.; Meucci, M.; Guidetti, L.; Baldari, C.
<x xml:space="preserve">Abstract</x> To examine the influence of different types of exertion on immediate and delayed attention in 116 primary school children divided in three groups of exertion [cognitive exertion – CE (school curricular lesson), physical exertion – PE (traditional physical education lesson), mixed cognitive and physical exertion – CPE (coordinative physical education lesson)]. CPE was the combination of physical load due to the practice of physical exercises and of cognitive load requested to perform movement‐based problem solving tasks requiring accurate timing, temporal estimations, temporal production, and spatial adjustments. Children's attentional capacity was tested before (pre) and after (at 0 min and at 50 min post) a CE, a PE, or a CPE lesson, using the d2‐test of attention, and analyzed using a 3 × 3 × 2 mixed analysis of covariance with exertion type and time as within factors, gender as between factor, and baseline data as covariate. Effect sizes were calculated as partial eta squared (ƞ2). Results showed that participants' attentional performance was significantly affected by exertion type (P < 0.0001), by time (P < 0.0001) and by exertion type × time interactions (P < 0.0001). The effect sizes ranged from medium (0.039) to large (0.437). Varying the type of exertion has different beneficial influences on the level of attention in school children.